Cole vegetables enhancing volume of vegetable basket - Kalia, Pritam; Singh, Shrawan; rakash, Chander; Sey, Shyam Sunder (Indian Horticulture, 2019)
Except cabbage and cauliflower, most of the cole crops are recent introduction in India and grown on limited scale during winter season in plains and during summer in hills. In fact, cauliflower and cabbage have spread extensively around the country, particularly after the development of heat tolerant tropical types. During 1990s, productivity of early cauliflower varieties was below 7-8 tonnes/ ha which has now surpassed 15 tonnes/ha with introduction of Pusa Meghna, Pusa Kartiki, Pusa Ashwini and Pusa Kartiki Sankar. This has benefited farmers across the north Indian plains with increased profitability. Improved varieties are also instrumental in spreading cauliflower to non-traditional areas such as south Indian states and tropical islands, ensuring year-round production. Similarly, tropical cabbage Pusa Ageti and its derived lines are instrumental in prolonging the fresh cabbage availability period and seed availability in India. Developments in broccoli and Brussels sprouts made them reach the common people in India ensuring nutritional security to our countrymen.